Infecção por Toxoplasma gondii promove a disfunção da barreira epitelial na linhagem de células Caco-2 - Briceño, Marisol Patricia Pallete (2015)
Toxoplasma gondii, a zoonotic Apicomplexa phylum parasite, is an obligate intracellular pathogen responsible for 10-50% of human infections worldwide. Cell invasion is essential for parasite surviving. Thus, it is expected that both parasite and host cell compounds help T. gondii succeed invasion at intestinal environment. Moreover, the mechanisms by which the parasite invades and disseminates through the gastrointestinal tract are not well established. We aimed to evaluate and determine some morphophysiologic modifications on the cell line Caco-2 during T. gondii infection. To accomplish this, we addressed to assess the effect on dextran endocytosis and paracellular permeability of infected cells, investigate the effect of T. gondii on Caco-2 microvilli (using phalloidin for actin detection) and tight junction integrity (by occludin detection) on this cell line. To establish whether T. gondii infection can modify the transepithelial electrical resistance (TEER), and IL-1β and IL-8 cytokines expression. Moreover, we took further to study the influence of Notch pathway in Caco-2 cells infected with this parasite. Our results show that dextran endocytosis is less in infected cells than in non-infected cells. Caco-2 brush border was disrupted due T. gondii infection showing a dissipation of microvilli at the cell surface. The infection outcome could be clearly observed by loss of microvilli when comparing non-infected cells. For evaluated the effect of T. gondii infection on occludin distribution, we performed immunofluorescences. Occludin was observed in a net pattern on control cells, however this patter is not well establish in the presence of the parasite. In addition, the protein localization was clearly lower at infected cells, compared to non-infected ones. TEER in Caco-2 cells infected decreased than in non-infected control. There was an increase in IL-8 and an increasing tendency in IL-1β mRNAs expression when Caco-2 cells were infected. Furthermore, intracellular proliferation of T. gondii diminishes in the presence of Notch pathway inhibitor. These results suggest the important influence of T. gondii invasion on the homeostasis of intestinal cells including tight junction and brush border integrity and, cell permeability leading loss of epithelia polarity. Nevertheless, further investigation using animal model is need to better understand the effect of T. gondii infection on polarity and cell surface.